Relationships between parental responsive feeding and infant appetitive traits: The moderating role of infant temperament - Liu, Yan; Kong, Yan; Li, Zhihui; Zhang, Guanghua; Wang, Lin; Yu, Guiling (Frontiers in Psychology, 2023)
Introduction Between the ages of 6 and 12 months is a crucial stage for children to develop appetitive self-regulation. Evidence suggests that a combination of parental responsive feeding and infant temperament (surgency, effortful control, negative affect) shapes infant appetitive traits (food approach, food avoidance). There is a need for research to explore these relationships, in order to provide guidance for the design of an effective intervention to improve appetitive traits. The objective of the current study was to explore the moderating role of infant temperament in the relationship between parental responsive feeding and infant appetitive traits. Methods A total of 616 questionnaires, measuring parental responsive feeding, infant appetitive traits, and infant temperament, were collected from parents with infants aged 6–12 months. Results Results revealed that responsive feeding was associated with both food approach and food avoidance. Furthermore, only lower levels of surgency significantly moderated the relationship between responsive feeding and food approach, while responsive feeding was associated with food avoidance irrespective of infant temperament. Discussion These findings suggest that a strategy embedding responsive feeding interventions should be adopted to reduce infant food avoidance and low-surgent infant food approach, and interventions that are tailored toward food approach for infants with effortful control, negative affect, or higher levels of surgency should be further sought.